Study of underwater laser communication - Tan, Chi Siong (2018)
Acoustic communication has been the main means of communication in the water medium, but it has multiple limitation such as, high delay, limited bandwidth, high bit error rate and high energy consumption. Modern communication such as submarine-to-submarine or submarine-to-satellite requires a technology beyond the limitation of acoustical technique. Laser communication provides a way of meeting the modern communication requirement of having higher bandwidth, higher data transfer rate, low power consumption with low delay. An extended study on underwater laser communication will provide details about the valuableness of underwater laser communication and provides a better comprehension so as to formulate the optimisation of system. This paper will provide extensive studies on components of underwater laser communication, different factors in water that affects transmission in terms of range, power and clarity. Simulation by MATLAB will be performed to replicate water conditions and serve to test out all different factors of water such as absorption and scattering.